Phatophysical, photochemical and bovine serum albumin binding studies on water-soluble gallium(III) phthalocyanine derivatives - Ogunsipe, Abimbola; Nyokong, Tebello; Durmuş, Mahmut (World Sci Publ Co Inc, 2007)
Spectral, photophysical, photochemical and bovine serum albumin binding studies on some gallium(III) derivatives - {1,(4)-(tetrapyridyloxyphthalocyaninato)gailium(III), (alpha GaPc);2,(3)-(tetrapyridyloxyphthalocyaninato)gailitim(III), (beta GaPc); and their quaternized derivatives: Q alpha GaPc and Q beta GaPc)} are hereby presented. beta-Substituted complexes are more fluorescent, but show lower tendencies to undergo intersystem crossing than the a-substituted, as judged by their fluorescence and triplet quantum yield values. The quaternized derivatives (QGaPc) are water-soluble and non-aggregated, which makes them potential photosensitizers of choice for photodynamic therapy applications; these amphiphilic compounds also bind strongly to bovine serum albumin in 1: 1 stoichiometries, and with binding constants (K,) in the order of 10(6) M-1. Copyright (C) 2007 Society of Porphyrins & Phthalocyanines.
Keywords: photophysics; photochemistry; photodynamic therapy; bovine serum albumin; Stern-Volmer equation